Association between non-highdensity lipoprotein cholesterol to high-density lipoprotein cholesterol ratio and cardiovascular-kidney-metabolic syndrome: evidence from NHANES 2001–2018 - Duan, Yang; Yang, Ke; Zhang, Tianai; Guo, Xiangsheng; Yin, Qianran; Liu, He (Frontiers in Nutrition, 2025)
ObjectiveThis research is to analyze the connection between NHHR and CKD occurrence using NHANES from 2001 to 2018. It will evaluate the feasibility of NHHR as a tool for predicting CKM syndrome and offer valuable insights for personalized treatment approaches within the U.S. population.MethodsData from 16,575 individuals aged 20 to 69 years were analyzed, having excluded those who were pregnant and individuals with incomplete data. CKM syndrome was characterized by the simultaneous presence of CKD and Cardiometabolic Syndrome (CMS). For the statistical analysis, weighted logistic regression models were applied, accounting for variables such as age, gender, ethnicity, educational background, marital status, lifestyle factors, and preexisting health conditions. Differently, restricted cubic splines (RCS) were applied to investigate any possible nonlinear relationships between NHHR and CKM in the study.ResultsThe research revealed that the occurrence of CKM syndrome was more prevalent among individuals aged 60 and older, with women representing 55.36% of those affected. Additionally, NHHR levels were notably elevated in CKM patients when compared to those without CKM (p < 0.0001). As NHHR increased, the prevalence of CKM also rose, with the highest prevalence in the highest NHHR quartile (Q4: 36.06%). A positive connection between NHHR and CKM was indicated by multivariable logistic regression, especially in the upper quartiles of NHHR (Q3 and Q4). Moreover, RCS analysis displayed a noteworthy nonlinear connection between NHHR and CKM occurrence. The subgroup analysis uncovered significant interactions influenced by BMI and Hypertension.ConclusionWith the rising global prevalence of CKM syndrome, early identification of high-risk individuals using NHHR could inform targeted prevention and intervention strategies. Future research should focus on validating NHHR in diverse populations and exploring its clinical utility, as well as examining its relationship with other biomarkers of metabolic dysfunction to better understand CKM syndrome’s complex pathophysiology.